Practical reflections on a collaboration with healthcare consumers on the development of a simulation. (9th October 2020) - Symon, Benjamin; Edwards, Rachel; Twigg, Sonia Jean; Ardila Sarmiento, Martha Carolina; Barwick, Stephanie
Abstract : Background: Healthcare simulations generate moments of 'cultural compression' through which we transmit core values about our professional identities and the families we care for. The engagement of healthcare consumers in this process is useful to evaluate the values we transmit and ensure authenticity in the narratives we share. Methods: A simulation package on febrile neutropenia and port access was written by healthcare staff in consultation with the parent of a child with leukaemia. Healthcare consumer review was focused on the representation of the simulated parent within the simulation scripts. The child and his mother assisted in the development of supportive video resources on family perspectives on port access and demonstration of the procedure. Results: The involvement of healthcare consumers in the development of the scenario had positive impact on the design and the supportive resources, both of which created opportunities for patient advocacy and reinforced the centrality of healthcare consumers within the healthcare team. Conclusions: Healthcare consumer collaboration in scenario design was achievable and impactful without significant increased cost. We hope to promote the benefits of healthcare consumer consultation in simulation design to improve the pursuit of educational and cultural learning objectives.